2014
DOI: 10.4028/www.scientific.net/msf.783-786.2541
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Shape Memory Alloys Based on Ti-Platinum Group Metals Compounds

Abstract: The effect of alloying to TiPd and TiPt on phase transformation temperature, phase equilibria, and shape recovery were investigated for TiPt and TiPd base high-temperature shape memory alloys. Ru, Ir, Co and Zr were chosen for additional elements and Zr was found as the most effective element to improve shape recovery of TiPd and TiPt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…At 50at%Ir, it is suggeted that the first martensitic transformation occurs around 1500 ˚C and the second martensitic transformation occurs between 700-800 ˚C. It indicates Ir addition becomes B2 phase unstable and expects increase of transformation temperature, however, Ir addition decreased transformation temperature gradually up to 12.5 at%Ir [12]. The martensite transformation temperature for 1 at% addition for most of alloying elements was less than 20 ˚C or around 20 ˚C as shown in Fig.…”
Section: Thermec 2016mentioning
confidence: 86%
See 2 more Smart Citations
“…At 50at%Ir, it is suggeted that the first martensitic transformation occurs around 1500 ˚C and the second martensitic transformation occurs between 700-800 ˚C. It indicates Ir addition becomes B2 phase unstable and expects increase of transformation temperature, however, Ir addition decreased transformation temperature gradually up to 12.5 at%Ir [12]. The martensite transformation temperature for 1 at% addition for most of alloying elements was less than 20 ˚C or around 20 ˚C as shown in Fig.…”
Section: Thermec 2016mentioning
confidence: 86%
“…Then, Co, Ru, and Ir can be fully soluble with TiPd. However, B2 structure of TiCo and TiRu is very stable and no martensitic transofmration occurs, then, it is also reasonable that marntensite tranformation temperature drastically decreases with increase of Co and Ru [12]. TiIr has two-step martensitic transformations such as B2 -> distorted B2 structure -> orthorombic structure in the composition rage between 48 and 52 Ir [13].…”
Section: Thermec 2016mentioning
confidence: 95%
See 1 more Smart Citation
“…The current author has published a number of papers related to nickel-free titanium based shape memory alloys for biomedical and engineering applications in international journals [78][79][80][81][82][83][84][85][86]. During postdoctoral work from 2012 to 2014 in the High Temperature Materials Unit, National Institute for Materials Science (NIMS), Tsukuba, Japan, the current author's research activities were related to TiPt and TiAu based intermetallics for high temperature applications and he has published papers in international journals [87][88][89][90][91][92][93][94].…”
Section: Biocompatibility Issues Of Nitinolmentioning
confidence: 99%
“…However, one problem of binary compounds is their low strength in the austenite phase, which results in a poor shape memory effect [14][15][16]. To increase the high-temperature strength of Ti-Pd [17,18], Ti-Au [19,20], and Ti-Pt [21][22][23][24][25], the addition of alloying elements has been attempted; this process is reviewed in [26][27][28]. It was found that an alloying element has some effect at improving the strength of the austenite and martensite phases, resulting in improved shape recovery.…”
Section: Introductionmentioning
confidence: 99%